Household Demand for Durable Goods: The Influences of Rates of Return and Wealth - Hess, Alan C. (The Review of Economics and Statistics, 1973)
They indicate that purchases of durable goods (DUR) are the third most volatile component behind inventory investment (INV I) and federal government expenditures (F GOV). The correlation coefficients between GNP and its components listed in the second row of table 1 show that durable goods purchases have the third hiighest covariance with GNP after inventory investment and nonresidential investment (NRI). Theoretically, these purchases represent either changes in the size of the household portfolio through changes in the flow of savings, or a reallocation of accumulated wealth among assets in response to changes in rates of return. Empirically, some effort has been given to examining the separate influences of rates of return and income. Hamburger (1967) found that interest rates, the price of durable goods relative to other prices faced by the consumer, and disposable personal income all have a significant impact on purchases of durable goods. portance of these variables as sources of fluctuation in purchases. Motley (1970) included a user cost of real assets variable in addition to the rate on savings deposits and expected income, and found in sharp contrast to Hamburger that none of them had a significant influence on the demand for the sum of durables and housing. The analysis of fluctuations in durable good purchases presented here differs from its prede-